Analisis Pengelolaan APBDes: Studi Di Desa Kadubeureum Kecamatan Pabuaran Kabupaten Serang Tahun 2024 - Saidi Saidi; Laeli Nur Khanifah; Farhan Ramadhan; Muhamad Fikri; Satrio Ramadhan (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
Corruption remains a longstanding issue that continues to draw attention—not only at the national and regional levels but also at the village level, which serves as the frontline of governance. Since 2015, the Indonesian government has disbursed Village Funds to promote rural development and welfare; however, misuse of these funds frequently occurs. This study focuses on Kadubeureum Village, Serang Regency, which in 2020 became the site of a corruption case involving village officials. A qualitative case study approach was employed, utilizing interviews, observations, and documentation. The findings reveal that community participation in the management of the Village Budget (APBDes) is relatively good, with active involvement from various village groups. However, transparency remains weak due to limited access to information and outdated budget information platforms. The management of the APBDes is not fully open to the public, which undermines community trust. These findings indicate that weak transparency, accountability, and oversight in APBDes management may contribute to the occurrence of corruption at the village level.